2022
DOI: 10.1097/bot.0000000000002241
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Locally Injected Tranexamic Acid in Hip Fracture Patients: A Retrospective Review

Abstract: Objective:To determine whether locally injected tranexamic acid (TXA) used in the surgical treatment of fragility hip fractures can lower transfusion rates without increasing the risk of complications.Design:Retrospective comparative cohort.Setting:Tertiary referral orthopaedic specialty hospital, Level I trauma center.Patients/Participants:A total of 490 patients (252 patients received TXA) 50 years of age and older who underwent surgery for a low-energy fragility fracture of the proximal femur between March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our group has also previously published data on the Local TXA and control groups included in this study before our conversion to IV TXA. 21 The data indicated that the Local TXA group saw a 10% reduction in blood transfusions compared with the control group that did not receive any TXA. The IV TXA group had a 22% reduction in blood transfusions compared with the control group and a 12% reduction in blood transfusions compared with the Local TXA group.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our group has also previously published data on the Local TXA and control groups included in this study before our conversion to IV TXA. 21 The data indicated that the Local TXA group saw a 10% reduction in blood transfusions compared with the control group that did not receive any TXA. The IV TXA group had a 22% reduction in blood transfusions compared with the control group and a 12% reduction in blood transfusions compared with the Local TXA group.…”
Section: Discussionmentioning
confidence: 96%
“…Our group has also previously published data on the Local TXA and control groups included in this study before our conversion to IV TXA. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation